농가단위 농업소득 안정에 관한 연구 - 박성재 (소득안정계정 도입방안에 관한 연구, 2006)
The study examined prerequisites for operating an agricultural income stabilization program and what contents the program needs to contain. At a time when the government considers enforcing such a program in 2009 or thereafter, we investigated various forms of an income stabilization policy and suggested a basic direction to which a related policy is supposed to be headed, while considering domestic agricultural conditions, policy changes in developed countries, and related WTO regulations. Because of not only the growing income fluctuation in farming caused by its unique characteristics and market opening but also the restrictions imposed by bilateral and multilateral trade negotiations on sustaining traditional income support programs, it is necessary to reform farm policies and come up with a solution to stabilize farm income. In this sense, agricultural income stabilization programs are becoming a key player, as Canada has already implemented and the U.S. is considering it. Canada recently changed its program from NISA to CAIS. In both programs, a farmer can choose an income protection level based on his risk aversion, financial conditions and the level of risks involved in his farming. NISA is similar to a savings account in a sense that it cumulates its own interests based on an amount farmers deposit in his or her NISA account. While CAIS is similar to an insurance in a sense that farmers pay a premium, its premium does not expire unless the program makes a payment. In our review of the two programs, we found that NISA is easier to operate than CAIS because it requires less information on farmers. However, CAIS is more effective in protecting farmers from severe income reductions. Since both programs have their own advantages, we designed two agricultural income stabilization programs; one is based on NISA and the other on CAIS. We also investigated the possibility of implementing the programs by taking into account the following factors: income index, ways to gather information on incomes, target farm tiers and commodities, and required budgets. If any of the two programs is enforced, we suggest that it will be available to every farmer. In addition, if a program is implemented only with respect to commodities, and with income information available, we suggest that such a program is better to be started with livestock and fruits since they are better prepared in many aspects. Also, it is inappropriate to cover rice in the program since limitations are placed on the current direct payment programs for rice and the income fluctuation of rice farming is relatively small. We suggested a candidate program for the trial operation of gathering information on farmers in operational and financial respects as they are key elements in the program. By carrying out a statistical analysis as well as a survey, we estimated a function of farm income fluctuation, income support levels, budget requirements in different income stabilization programs, and accounting ability of farmers. A NISA type program requires a smaller budget than that of a CAIS type under a same protection level. When 50% of livestock and fruit farmers are registered in the programs, it is estimated that a NISA type needs a budget of 85.4 billion won while a CAIS type needs 140.8 billion won. Along with budget requirements, a farmer's share in a program and the level of effects from income compensation are key factors in the government's choosing a program. Before making a decision, it is also required for the government to fully review the linkage among an income stabilization program, direct payments, disaster insurances and other income compensation programs in an effort to raise the efficiency of a farm income policy. Researcher: Seong-Jae Park, Nae-Won Oh, Tae-Gon Kim, Joon-Ki Park, Ho-Gun Chong, Suhk-Hyun Kim, Han-Pil Moon, and Yong-Won Cho E-mail Address: seongjae@krei.re.kr, neawonoh@krei.re.kr, taegon@krei.re.kr, jkpark@krei.re.kr, hogunc@krei.re.kr, shane@chonnam.ac.kr, hanpil@krei.re.kr, cyw00@krei.re.kr